Deviation of the visual and intellectual path of the press photo in magazine covers designs (Al-Academy, 2024)
System repercussions of the modern scientific and cognitive system lead design and concept to the application of a type of organized strategy to achieve a high level of aesthetic and cognitive creation. Therefore, it becomes necessary to employ visual language expressive of the image in line with the cognitive aspects representing part of those System repercussions. Consequently, what visual and intellectual paths carry in terms of implicit and apparent languages form a nerve to generate understanding and interpretation to achieve communication. Research problem: What are the deviations realized by the visual and intellectual paths of the journalistic image in magazine cover designs? Research objective: To uncover the deviation of the visual path of the journalistic image and its reflections on changing the intellectual path in magazine cover designs. Key findings: The use of Symbolic shorthand in magazine cover designs to model number (3) showed the possibility of simplifying the visual context of the image, which in turn reflected on simplifying and enhancing the intellectual path to achieve communicative dimension. Conclusions: The visual path of the image actively contributed to deviating the intellectual path towards interpretive and analytical trends carrying implicit semantic depth beyond the apparent semantic meaning of the image.